Characterization of waste fabric fiber-reinforced wood-plastic composites - Eksi, Basak Nur; Gulec, Aylin; Karatay, Halil; Arpaci, Emrecan; Uysal, Mesut (Taylor & Francis Ltd, 2025)
This study aimed to explore the feasibility of incorporating waste fabric fibers into polylactic acid (PLA)-based wood plastic composites (WPCs). Unlike conventional WPC with randomly dispersed fibers, a multilayer design was employed with waste fabric fibers. Composites were fabricated by using twin-screw extrusion and then hot-pressing. Mechanical, thermal, water absorption, chemical, and morphological properties were systematically evaluated using mechanical tests, TGA, FTIR, and SEM. The multilayer configuration significantly improved strength, accordingly, advantage of a controlled reinforcement-layer design was demonstrated compared to non-reinforced sample groups. The results showed that adding 5% wood content to fabric fiber-reinforced PLA increased flexural strength by 28% and tensile strength by 24% compared to neat PLA. However, higher wood contents (10% and 15%) reduced strength by 12-18% due to poor dispersion and weak interfacial adhesion. Thermal stability improved by approximately 15 degrees C, while water absorption decreased by nearly 20% in fabric fiber-reinforced composites relative to those of higher wood content. This study demonstrated that textile waste can be successfully upcycled into high-performance, bio-based composites, providing both structural improvements and environmental benefits. These results highlight the potential of textile waste as an effective reinforcement in WPC, promoting circular economy practices and offering a sustainable alternative for various industrial applications.
Keywords: Wood-plastic composites; reinforcement; flexural properties; tensile strength; thermal degradation; water absorption